Strategies to safely target widely expressed soluble adenylyl cyclase for contraception - Ferreira, Jacob; Levin, Lonny R.; Buck, Jochen (Frontiers in Pharmacology, 2022)
In humans, the prototypical second messenger cyclic AMP is produced by 10 adenylyl cyclase isoforms, which are divided into two classes. Nine isoforms are G protein coupled transmembrane adenylyl cyclases (tmACs; ADCY1-9) and the tenth is the bicarbonate regulated soluble adenylyl cyclase (sAC; ADCY10). This review details why sAC is uniquely druggable and outlines ways to target sAC for novel forms of male and female contraception.